1996
DOI: 10.1126/science.273.5280.1380
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Host-Microbial Interactions in an Open Mammalian Ecosystem

Abstract: The maintenance and significance of the complex populations of microbes present in the mammalian intestine are poorly understood. Comparison of conventionally housed and germ-free NMRI mice revealed that production of fucosylated glycoconjugates and an alpha1, 2-fucosyltransferase messenger RNA in the small-intestinal epithelium requires the normal microflora. Colonization of germ-free mice with Bacteroides thetaiotaomicron, a component of this flora, restored the fucosylation program, whereas an isogenic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
427
1
8

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(448 citation statements)
references
References 21 publications
12
427
1
8
Order By: Relevance
“…Although generally regarded as a beneficial group, higher numbers of lactobacilli have been implicated in broiler growth depression owing to competition for nutrient uptake or impaired fat absorption linked to deconjugation of bile acids (Torok et al, 2011b). Meanwhile, species from the Bacteroidetes family are involved in many important metabolic activities including fermentation of carbohydrates, induction of critical glycolytic enzymes in the enterocytes, utilization of nitrogenous substances, biotransformation of bile acids and prevention of pathogen colonization (Bry et al, 1996;Phillips, 2009). In summary, according to the literature and the current results, it could be concluded that a decrease in the numbers of some bacterial groups such as enterobacteria, and probably lactobacilli, accompanied by an increase in others such as bacteroides in the intestine might be related to improved performance in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…Although generally regarded as a beneficial group, higher numbers of lactobacilli have been implicated in broiler growth depression owing to competition for nutrient uptake or impaired fat absorption linked to deconjugation of bile acids (Torok et al, 2011b). Meanwhile, species from the Bacteroidetes family are involved in many important metabolic activities including fermentation of carbohydrates, induction of critical glycolytic enzymes in the enterocytes, utilization of nitrogenous substances, biotransformation of bile acids and prevention of pathogen colonization (Bry et al, 1996;Phillips, 2009). In summary, according to the literature and the current results, it could be concluded that a decrease in the numbers of some bacterial groups such as enterobacteria, and probably lactobacilli, accompanied by an increase in others such as bacteroides in the intestine might be related to improved performance in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that certain commensal bacteria may be necessary for the development of the intestine to its full absorptive capacity. B. thetaiotaomicron also directs the increased expression of terminal a-linked fucose by enterocytes positioned in the distal small intestine (Bry et al, 1996). These changes in host glycan expression allow the bacterium to expand its colonization niche to additional areas along the small intestine and also augment colonization by other commensal members of the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…However, the drastic change in diet composition at weaning might also induce modifications in the intestinal microflora. By comparing genetically identical germ-free mice with mice raised with a functional microbiota, Bry et al [39] have shown that the production of fucosylated glycoconjugates, appearing in the small intestine and colon after the age of weaning, requires components of the microbiota. Fucoconjugates are largely absent from weaned germ-free mice ; inoculation with flora restored the same fucosylation pattern as in conventional mice and induced an accumulation of α-1,2-fucosyltransferase mRNA.…”
Section: Discussionmentioning
confidence: 99%